Potential therapeutic role of pyroptosis mediated by the NLRP3 inflammasome in type 2 diabetes and its complications - Li, Xiang; Xiao, Gui-Ying; Guo, Tao; Song, Yu-Jie; Li, Qiu-Mei (Frontiers in Endocrinology, 2022)
As a new way of programmed cell death, pyroptosis plays a vital role in many diseases. In recent years, the relationship between pyroptosis and type 2 diabetes (T2D) has received increasing attention. Although the current treatment options for T2D are abundant, the occurrence and development of T2D appear to continue, and the poor prognosis and high mortality of patients with T2D remain a considerable burden in the global health system. Numerous studies have shown that pyroptosis mediated by the NLRP3 inflammasome can affect the progression of T2D and its complications; targeting the NLRP3 inflammasome has potential therapeutic effects. In this review, we described the molecular mechanism of pyroptosis more comprehensively, discussed the most updated progress of pyroptosis mediated by NLRP3 inflammasome in T2D and its complications, and listed some drugs and agents with potential anti-pyroptosis effects. Based on the available evidence, exploring more mechanisms of the NLRP3 inflammasome pathway may bring more options and benefits for preventing and treating T2D and drug development.